2004
DOI: 10.1603/0022-0493-97.5.1595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Efficacy of Insecticides to Differential Grasshopper (Orthoptera: Acrididae)

Abstract: The effect of temperature on activity of insecticides for controlling grasshoppers in leafy green vegetables was evaluated. Insecticides evaluated had differing modes of action and included diflubenzuron, azadirachtin, Beauveria bassiana, spinosad, endosulfan, esfenvalerate, and naled. We evaluated these insecticides for efficacy to third instars of differential grasshopper, Melanoplus differentialis (Thomas), at temperatures ranging from 10 to 35 degrees C. In the laboratory, treatment with esfenvalerate resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 5 publications
1
29
1
1
Order By: Relevance
“…The results of related research showed that the activity of azadirachtin on the differential grasshopper, Melanoplus differentialis [Thomas], does not depend on air temperature (Amarasekare & Edelson, 2004). Our results are not in accordance with the findings of the authors, while azadirachtin showed the highest efficacy on all three developmental stages of Colorado potato beetle at 208C.…”
Section: Resultscontrasting
confidence: 98%
“…The results of related research showed that the activity of azadirachtin on the differential grasshopper, Melanoplus differentialis [Thomas], does not depend on air temperature (Amarasekare & Edelson, 2004). Our results are not in accordance with the findings of the authors, while azadirachtin showed the highest efficacy on all three developmental stages of Colorado potato beetle at 208C.…”
Section: Resultscontrasting
confidence: 98%
“…This is in agreement with other studies finding species specific effects of multiple stressors3031, suggesting that the exact effects of interactions depend on the experimental setup, as well as on the species investigated. This highlights the potential problems of extrapolating results from studies investigating interactions on one species to, e.g., community scale or to ecological risk assessments12, and thereby emphasizing the need for further studies using standardised methods and/or multiple species.…”
Section: Discussionsupporting
confidence: 92%
“…Orshan et al (2006) suggested the high temperatures, blowing dust, and intense radiation found in parts of Israel limit the efÞcacy of residual insecticides, whereas Kiss and VirĂĄg (2009) and Uyanik and Ozdemir (1999) demonstrated higher intensities of ultraviolet light and warmer ambient temperatures, respectively, increased the degradation of insecticides. Amarasekare and Edelson (2004) reported the residual activity of endosulfan, naled, esfenvalerate, and spinosad decreased with increasing time (0 Ð24 h) after exposure to sunlight and high summer temperatures, whereas Tietze et al (1996) found the half-life of naled was reduced from 8 to 1Ð1.2 h by direct sunlight. As reported by Colacicco-Mayhugh et al (2011) andColeman et al (2006), environmental conditions at TAB were harsh during the period in which we evaluated the various control measures, with high temperatures and winds frequently creating dust storms from the talcum-like silt that blanketed the base and surrounding area.…”
Section: Discussionmentioning
confidence: 99%